The use of Tutoplast implants in the treatment of benign neoplasms and tumour-like lesions of bones in children - Baev, Vitaliy; Shevchenko, Stanislav; Vyrva, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The purpose of the present research was to analyse the experience of using Tutoplast implants for determining their place in the surgical treatment of benign tumours and tumour-like lesions in children. For the analysis, 26 clinical cases were chosen. We found out that the osteoinductive and osteoconductive properties of this material had the most balanced proportion for its usage in childhood orthopaedic practice. The obtained data demonstrate good prospects for using Tutoplast implants in the treatment of the above category of diseases.